2021
DOI: 10.3389/fped.2021.651995
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Genetic Etiology of Children With Developmental Language Disorder

Abstract: Objective: Developmental language delay (DLD) is one of the most common disabilities in childhood and can negatively affect a child's communication skills and academic and/or psychosocial development. To date, an increasing number of causative genes have been identified by diagnostic techniques like next generation sequencing. An early genetic diagnosis is important to properly prepare and counsel children and parents for possible future difficulties. Despite this, genetic assessment is usually not part of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Developmental language disorder (DLD) and other neurodevelopmental disorders (NDD) share many symptoms and signs (Nitin et al 2022 ; Plug et al 2021 ). DLD is a neurodevelopmental communication disorder characterized by persistent deficits in receptive and expressive language not attributable to other biomedical conditions and results in functional, psychological, social, and/or occupational limitations (American Psychiatric Association 2022 ; Bishop et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Developmental language disorder (DLD) and other neurodevelopmental disorders (NDD) share many symptoms and signs (Nitin et al 2022 ; Plug et al 2021 ). DLD is a neurodevelopmental communication disorder characterized by persistent deficits in receptive and expressive language not attributable to other biomedical conditions and results in functional, psychological, social, and/or occupational limitations (American Psychiatric Association 2022 ; Bishop et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used the term genomic DLD when referring to DLD caused by copy-number variants (CNVs). An increasing number of high-impact copy CNVs and rare variants have been identified in a proportion of DLD individuals (Chen et al 2017a , b ; Eising et al 2019 ; Kalnak et al 2018 ; Mountford et al 2022 ; Plug et al 2021 ; Villanueva et al 2015 ). The recent advances in sequencing technologies and the availability of population-level variations data have enabled genetic diagnosis in DLD and the discovery of new genes implicated in the condition (Mountford et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The boundaries between developmental language disorder (DLD) and other neurodevelopmental disorders (NDD) are not well de ned as they share many symptoms/signs (Nitin et al, 2022;Plug et al, 2021). DLD is a neurodevelopmental communication disorder characterized by persistent de cits in receptive and expressive language not attributable to other biomedical conditions and results in functional, psychological, social, and/or occupational limitations (American Psychiatric Association, 2022; Bishop et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The recent advances in sequencing technologies and the availability of population-level variations data have enabled genetic diagnosis in DLD and the discovery of new genes implicated in the condition (Mountford et al, 2022). Yet, some challenges exist, including the considerable phenotypic and genetic overlap between DLD and other NDD, as multiple genes implicated in the pathogenesis of DLD have also been implicated in other NDD (Mountford et al, 2022;Plug et al, 2021). Furthermore, disentangling the polygenic contribution in DLD is lagging compared to the monogenic forms.…”
Section: Introductionmentioning
confidence: 99%
“…Further work is needed to see whether the anatomical differences discovered by Krishnan et al and others cause DLD: in an association study like this, it is equally possible that DLD is responsible for the observed brain changes. In addition, it remains to be seen whether the molecules responsible for the reduced levels of myelin found in the basal ganglia and Broca’s area are coded by genes that have already been implicated in DLD ( Plug et al, 2021 ).…”
mentioning
confidence: 99%